Diagnosis dan Tata Laksana Glaukoma - Nugroho Nitiyoso (PT Kalbe Farma Tbk., 2024)
Glaucoma is one of the most common causes of blindness in the world. The most common type is open-angle glaucoma. In open-angle glaucoma, intraocular pressure slowly rises, causing nerve damage which will gradually narrow the visual field. Treatment involves surgical as well as medical options. Several classifications of drugs with different mechanisms of action can be combined. Several treatment options will be discussed in this article.